Mediastinal abscess following iatrogenic piriform fossa perforation - case report - Ribeiro, Susana (2010)
The hypopharynx and cervical oesophagus are particularly vulnerable areas of injury resulting from endotracheal intubation. These anaesthesia accidents are uncommon, rarely reported and its incidence is higher in the emergency situation. The pharyngoesophageal perforations may stay unnoticed until characteristic signs and symptoms are present, such as cervical pain, fever, dysphagia, leukocytosis, subcutaneous emphysema and pneumomediastinum. Surgical treatment vs conservative treatment is controversial. It is agreed, however, that the time interval between the initial trauma and diagnosis and treatment is the single most important factor affecting outcome. We report a case of mediastinal abscess following piriform fossa perforation occurring after a difficult intubation for an emergent caesarean delivery.